MATHEMATICAL MODELING AND Z-CONTROL MECHANISM TO MITIGATE CHLAMYDIA TRACHOMATIS-INDUCED CONJUNCTIVITIS IN NEWBORNS - Shah, Nita H; Vaghela, Jalpa N; Jayswal, Ekta N. (International Journal of Engineering Science Technologies, 2025)
This study analyzes a mathematical model employing a Z-control mechanism to prevent neonatal Chlamydial conjunctivitis in newborns of infected mothers. Chlamydia trachomatis transmission during delivery can lead to conjunctivitis and severe complications in the lungs and nasopharynx if untreated. The model, based on nonlinear differential equations, evaluates the basic reproduction number at the disease-free equilibrium point. Numerical simulations demonstrate that Z-control effectively stabilizes chaotic oscillations in the system, reducing the risk of conjunctivitis in newborns. The findings highlight that prenatal testing, early treatment of pregnant women, and newborn screening are critical for preventing and controlling Chlamydia transmission. The implementation of Z-control has proven effective in mitigating this epidemic, significantly reducing the incidence of neonatal Chlamydial conjunctivitis.